(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The development of creative potential in the visual arts is essential for fostering innovative thinking and artistic expression among students. This study outlines a comprehensive methodology for identifying and nurturing students’ creative potential within visual arts education. The methodology integrates diagnostic assessments, including observational techniques, portfolio reviews, and creativity-focused tasks, to identify students’ innate artistic abilities and creative thinking patterns. Development strategies emphasize individualized instruction, interdisciplinary projects, and collaborative learning environments to enhance creative skills. By incorporating reflective practices and iterative feedback, the approach ensures sustained growth in students’ artistic confidence and originality. The methodology was piloted in a diverse classroom setting, demonstrating measurable improvements in students’ creative output and problem-solving abilities. This framework provides educators with practical tools to cultivate creativity, preparing students for lifelong engagement with the visual arts.